Clinical Nurses’ Perceptions of Change Agent Competency for Quality Improvement in Nursing Practice: A Qualitative Study - Ramkaew, Kamonpan; Phumdoung, Sasitorn; Boonyoung, Nongnut (Pacific Rim International Journal of Nursing Research, 2024)
Changes in the healthcare system directly impact the nursing profession. Nursing is a vital profession, and nurses face many challenges and the need for changes in healthcare. This first-time study aimed to describe the change agent competency of clinical nurses from their perspectives in the Thai healthcare context. The researchers conducted a qualitative descriptive study. In-depth interviews were conducted among 12 clinical registered nurses in a Thailand Quality Award recipient super-tertiary university hospital in southern Thailand using semi-structured interviews, audio-recording, and observation record forms during October to December 2021. Purposive and snowball sampling were used to select participants. Using content analysis, seven themes of change agent competency were revealed: 1) improving quality of care, 2) commitment to achieving change, 3) clinical ability, 4) enhancing engagement in improvement, 5) using information efficiently, 6) knowing how to seek useful resources, and 7) improving after receiving feedback contributing to the conceptual structure of change agent competency. Trustworthiness was assessed using member checking and peer debriefing to ensure the quality of the study. The findings are helpful for nurses and health leaders to better understand the potential of nurses as change agents in reforming practice. The findings of this study also form a foundation for nurse educators to incorporate change agent theory and practices in education and training. However, since this was a first time study on the topic with clinical nurses in Thailand, much more research is needed, including developing a standard tool to measure and develop change agent competency of Thai clinical nurses, given there is no such instrument in the country